REGION AND NATION: THE INSURGENT RIO GRANDE BETWEEN THE BRAZILIAN EMPIRE AND THE RIVER PLATE’S REPUBLICS (1838-1842) - Bossak de Figuereido, Joana; Barcellos Guazzelli, César A. (Revista de Historia Social y de las Mentalidades, 2013)
The ninteenth century was marked by the decolonization process and the consequent national state formation process in Latin- America. During many years the civil wars between the different political groups were the most visible characteristic of those times. The present article seeks an explanation to the secession of the Brazilian province of Rio Grande do Sul, located in the extreme south of the country, in the frontier with the Oriental State of Uruguay and the Argentine Confederation. The insurgents proclaimed their independence from the Empire of Brazil under the name of Riograndense Republic, managing to establish right away political and economical commitments with the neighboring republics as a way of securing itself against the Brazilian government’s efforts to reintegrate his former province. The Riograndense Republic maintained itself from 1836 to 1845, yet the text shows the most important diplomatic acts of the rebels, which occurred between 1838 and 1842.